Raccomandazioni per lo sviluppo dell'Editoria Elettronica negli Atenei Italiani - Cotoneschi, Patrizia; Pepeu, Giancarlo (Firenze University Press, 2006)
In May 2004, the delegates of the Library Commission of the CRuI had already identified the issue of electronic publishing as one of the strategic aspects to be addressed and explored with the utmost attention. The setting up of the working group on Electronic Publishing, co-ordinated by the University of Florence, formalised this interest, stimulating the analysis of the state of the art in this field in Italy, the opportunities which it offered to the academic world and the definition of possible lines of development. The "Recommendations" comprised in this publication are addressed to the delegates of the Chancellors of the Italian universities and their collaborators, and intended to provide information and suggestions for the development of electronic publishing initiatives. They are consequently designed not only as a tool for help and guidance for those who are already moving in the direction of a University publishing initiative, but also as an invitation to reflect on the importance that electronic publishing is acquiring for the teaching and scientific activities of the future.